Documentation errors in transfusion chain: Challenges and interventions. (August 2020) - Moiz, Bushra; Siddiqui, Arsalan Kabir; Sana, Nazish; Sadiq, Muhammed Wahhaab; Karim, Farheen; Ali, Natasha
Abstract: Background and objective: There are several steps in transfusion chain where accurate documentation is critical. This study was conducted to evaluate the frequency of documentation errors during transfusion process and to evaluate the effectiveness of interventions in error-management. Methods /Material: This study was conducted at Aga Khan University, Pakistan during 2016–2018. Transcription and bedside documentation errors were identified from in-house computerized system and from medical charts. Raw WBIT rate was calculated for repeat blood samples and adjusted for frequencies of ABO-groups in our population accounting for silent WBIT. Rate of ABO-mismatched red cell transfusions was calculated for the annual totals of red cell transfusions. Chi-square was used for observing relationship among errors of various data sets. Results: A total of 43 WBIT was identified during 54, 219 repeat blood samples where blood group was already defined in blood bank information system. Annual unadjusted and cryptic WBIT rate was consistent at 0.8 and 0.6 per 1000 samples respectively during 2016–2018 (p 0.859). There were 1161 transcription errors (1.1 %) in blood group documentation in 105, 064 blood samples received for arranging blood products. ABO-mismatched transfusion rate was 0.9 for 10, 000 RBC transfusions in pre- and decreased to 0.4 in post-typing era. Overall, the compliance for completing checklist, correct ABO technique and appropriate ABO-interpretation was 88 %, 40 % and 24 % in the reviewed medical charts. Conclusions: Sample labeling errors were not improved through training or counseling. Bedside ABO-typing and checklist prior to blood transfusion can control the ABO-mismatched transfusion if done timely and correctly.